Conceptualising risk assessment and management across the public sector : from theory to practice - Murray, Jennifer; Enang, Iniobong (Emerald Publishing Limited, 2022)
Risk assessment and risk management are essential across the public sector to improve processes and outcomes. However, there is little clarity over what this actually means. This lack of understanding leads to a wide variation in risk assessment and management practice and to miscommunications of risk across professions, creating further barriers to interprofessional practice and co-creation of value across the public sector. Despite these challenges, there is a concurrent expectation that risk assessment and risk management be carried out across the sector to the highest standard, which inevitably becomes problematic. Conceptualising Risk Assessment and Management across the Public Sector explores concepts and applications of risk across the public sector to aid risk professionals in establishing a clearer understanding of what risk assessment and management is, how they might be unified across the sector, and how and where deviations across professions are needed. This book addresses these issues through providing a theory-informed discussion on the conceptualisations of risk, risk assessment, and risk management across the public sector, and through identifying where shared values and where differences exist across professions. Guidance on interprofessional risk practice and risk communication to overcome barriers is offered using a combination of theoretically underpinned approaches and exemplars from practice, presented to have broad applicability across the public sector rather than being siloed within a specific professional grouping or theoretical paradigm.
Keywords: Risk management.; Administrative agencies -- Management.; Business & Economics -- Finance -- Financial Risk Management.; Risk assessment.; elektronické knihy; electronic books